Librarians’ technological competence, performance, expectancy, and perceived ease of the use of automation software in academic libraries in Ogun State (Lead City International Journal of Library, Information & Communication Sciences, 2025)
This study examined librarians’ technological competence, performance, expectancy, and perceived ease of the use of automation software in academic libraries in Ogun state. A descriptive survey research design was adopted for this study. The total enumeration method was employed to select 104 respondents for the study. A self-designed and close-ended questionnaire was used as the instrument for gathering data from the respondents. The data gathered was analyzed using descriptive statistics such as frequency counts, percentages, mean, and standard deviation.Findings revealed there was a high level of librarians’ technological competence of librarians. There was a high level of librarians’ performance expectancy of automated software. The perceived ease of the use of automation software was high. The study revealed that the major problems affecting the use of automation software by librarians are frequent virus attacks, non-compatibility of the software, inadequate technical support of the automation software, and limited user community. It was therefore recommended that librarians should enhance ongoing professional development programs to keep librarians abreast of the latest advancements in automation software, ensuring they stay proficient and adaptable in the rapidly evolving technological landscape.